Constitutional basis of Austria’s accession to the European Union - E. A. Vodyanitskaya (Vestnik MGIMO-Universiteta)
On 1 January 1995 Austria became a member of the European Union. Austria’s accession to the EU constituted the most important transfer of jurisdiction in the history of the Federal Constitution. On this occasion the Austrian legislature passed an amendment to the Federal Constitution which provides for the participation of Austrian organs in the decision-making process of the European Union. The legal basis of Austria’s membership in the EU is the treaty on accession to the European Union and the special constitutional bill authorizing the competent authorities to ratify the treaty on accession. First of all, provisions on the election of Austrian members to the European Parliament were introduced by the amendment into the Constitution. Secondly, the amendment contains a procedure for participation of the Austrian lands and local governments in the decisions of the European Union. Thirdly, the legislative bodies on the central government level (National Council and Federal Council) are also accorded the right to participate in decision-making of the EU. Finally, a special provision confirming Austria’s participation in the Common Foreign and Security Policy of the Union was introduced.